Unprecedented Bifunctional Chemistry of Bis(acyl)phosphane Oxides in Aqueous and Alcoholic Media. Issue 38 (12th June 2019) - Schmallegger, Max; Eibel, Anna; Menzel, Jan P.; Kelterer, Anne‐Marie; Zalibera, Michal; Barner‐Kowollik, Christopher; Grützmacher, Hansjörg; Gescheidt, Georg
Abstract: Tailor‐made photoinitiators play an important role for efficient radical polymerisations in aqueous media, especially in hydrogel manufacturing. Bis(acyl)phosphane oxides (BAPOs) are among the most active initiators. Herein, we show that they display a remarkable photochemistry in aqueous and alcoholic media: Photolysis of BAPOs in the presence of water or alcohols provides a new delocalized π‐radical, which does not participate in the polymerization. It either converts into a monoacylphosphane oxide acting as a secondary photoactive species or it works as a one‐electron reducing agent. Upon the electron‐transfer process, it again produces a dormant photoinitiator. We have established the structure and the chemistry of this π radical using steady‐state and time‐resolved (CIDEP) EPR together with ESI‐MS, NMR spectroscopy, and DFT calculations. Our results show that bis(acyl)phosphane oxides act as bifunctional reagents when applied in aqueous and alcoholic media. Abstract : Tailor‐made photoinitiators play an important role for efficient radical polymerizations in aqueous media, especially in hydrogel manufacturing. Bis(acyl)phosphane oxides (BAPOs) are among the most active initiators. Herein, we show that they display a remarkable photochemistry in aqueous and alcoholic media (see figure)